Pengemasan Pesan Pelestarian Kain Tradisional Indonesia di Media Sosial Instagram @Pemudaberkain - Nabilah Puspita Ardhani; Augustin Mustika Chairil (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Social media, such as Instagram, has become an essential tool in raising awareness of social issues such as cultural preservation. The @pemudaberkain account is an initiative move that utilizes Instagram to reintroduce traditional Indonesian fabric into everyday life. The goal and focus of the @pemudaberkain account is to attract the interest of the younger generation in appreciating and using traditional Indonesian fabric. This study employs a qualitative content analysis method to examine how the preservation message is conveyed on the @pemudaberkain account during the period from November 2023 to July 2024. The findings show that @pemudaberkain utilizes various forms of content, including informative and persuasive messaging, to influence behavior change, encouraging audiences to adopt traditional fabrics both in formal occasions and casual styles. The @pemudaberkain account also collaborates with influence and external parties to expand its audience reach. Using the social marketing approach by Philip Kotler, @pemudaberkain aims to spread the idea of cultural preservation. Furthermore, @pemudaberkain has effectively used Instagram as a medium of cultural preservation, as evidenced by the positive audience responses, such as praise-filled comments, and audience’s behavior shift toward wearing traditional Indonesian fabrics as part of their everyday attire.